Fresh and Recirculated Submarine Groundwater Discharge Evaluated by Geochemical Tracers and a Seepage Meter at Two Sites in the Seto Inland Sea, Japan - Toshimi Nakajima; Ryo Sugimoto; Osamu Tominaga; Masaru Takeuchi; Hisami Honda; Jun Shoji; Makoto Taniguchi (Hydrology, 2018)
Submarine groundwater discharge (SGD) consists of fresh submarine groundwater discharge (FSGD) and recirculated submarine groundwater discharge (RSGD). In this study, we conducted simultaneous 25-hour time-series measurements of short-lived 222Rn and 224Ra activities at two sites with differing SGD rates in the central Seto Inland Sea of Japan to evaluate SGD rates and their constituents. At both sites, we also quantified the total SGD, FSGD, and RSGD using a seepage meter to verify the water fluxes estimated with 222Rn and 224Ra. SGD rates estimated using 222Rn and 224Ra at the site with significant SGD approximated the total SGD and RSGD measured by the seepage meter. However, SGD rates derived using 222Rn at the site with minor SGD were overestimated, since 222Rn activity at the nearshore mooring site was lower than that in the offshore area. These results suggest that the coupling of short-lived 222Rn and 224Ra is a powerful tool for quantification of FSGD and RSGD, although it is important to confirm that tracer activities in coastal areas are higher than those in offshore.